2018
DOI: 10.1002/pssa.201701014
|View full text |Cite
|
Sign up to set email alerts
|

Electrical, Optical, and Structural Characteristics of CH3NH3PbI3Perovskite Light‐Emitting Diodes

Abstract: Electrical, optical, and structural characteristics of perovskite light-emitting diodes (PeLEDs) are investigated. The PeLED consisting of ITO/ZnO/MAPbI 3 (CH 3 NH 3 PbI 3 )/spiro-OMeTAD/Ag structures shows a peak emission wavelength of 766 nm, turn-on voltage of 1.7 V, reverse breakdown voltage of À5.4 V, current efficiency of 1.5 Â 10 À4 cdA À1 , maximum luminance of 0.1 cdm À2 , and an external quantum efficiency of 0.2% at bias voltage of 3 V (or a current density of 617 mA cm À2 ). The PeLED also shows a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…[ 66 ] Different electron transport layers also significantly affect V RB . It is found that the breakdown voltage of the device with the structure ITO/ZnO/MAPbI 3 /spiro‐OMeTAD/Ag can reach −5.4 V, [ 11 ] which is similar with that of the PCBM ETL based PSC and far greater than TiO 2 based PSCs (about −0.5 V), as shown in Table 1. [ 11,30,31 ] Xiong et al.…”
Section: Currently Reported Strategies For Improving the Reverse Bias...mentioning
confidence: 82%
See 3 more Smart Citations
“…[ 66 ] Different electron transport layers also significantly affect V RB . It is found that the breakdown voltage of the device with the structure ITO/ZnO/MAPbI 3 /spiro‐OMeTAD/Ag can reach −5.4 V, [ 11 ] which is similar with that of the PCBM ETL based PSC and far greater than TiO 2 based PSCs (about −0.5 V), as shown in Table 1. [ 11,30,31 ] Xiong et al.…”
Section: Currently Reported Strategies For Improving the Reverse Bias...mentioning
confidence: 82%
“…It is found that the breakdown voltage of the device with the structure ITO/ZnO/MAPbI 3 /spiro‐OMeTAD/Ag can reach −5.4 V, [ 11 ] which is similar with that of the PCBM ETL based PSC and far greater than TiO 2 based PSCs (about −0.5 V), as shown in Table 1. [ 11,30,31 ] Xiong et al. [ 96 ] inserted a NdCl 3 interlayer at the perovskite/ETL interface and found that it not only blocked the migration of I − to the ETL but also resulted in a decreased defect density of the perovskite layer.…”
Section: Currently Reported Strategies For Improving the Reverse Bias...mentioning
confidence: 82%
See 2 more Smart Citations
“…[ 10–12 ] Other applications based on perovskite such as photodetectors, lasers, and light‐emitting diodes have also been widely studied. [ 13–17 ]…”
Section: Introductionmentioning
confidence: 99%